A study of some economic traits in a herd of Kenana cattle (North Sudan Zebu). II. Age at first calving and effects of improved nutrition on body development and sexual maturity - El-Khidir, O.A.; Khalifa, H.A.A.; Khalafallah, A.M.; Gaili, E.S.E. (Wiley, 1979)
The work reported in this paper was initiated to estimate the age at first calving in herd of Kenana cattle with particular reference to the influence of year and season of the birth on age of heifers at calving. It included a feeding trail to elucidate the effects of improved nutrition on body development and sexual maturity of Kenana heifers. The mean age at first calving was found to be 45.2±7.6 months. The study revealed significant (p